PENEGAKAN HUKUM PIDANA TERHADAP PELAKU YANG MEMPEKERJAKAN ANAK BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK DI KOTA PEKANBARU - Lesbon Manik; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Protection of law to child can be interpreted as effort protection of law to various child basic rights and freedom and also various importance related to prosperity of child. In order to giving protection to child, government have attempts children forbidden to work. Children prohibited to work because child pertained need protection to its rightss like education, growth of physical, resting, associating with with child which coeval and playing, growth of talent, and its intellegence storey for the shake of development of himself. In Pekanbaru Town Badness to worker of child increasing because employing controlled easy and cheaper child, badness of economic exploitation to child impinge rule based law protection of child.The purpose of this thesis , namely: First, the implementation of the enforcement of the criminal law agains to companies employing “children workers” based law Number 23 of 2002 about Protection of child in the Pekanbaru city, Second, what obstacles faced in enforcing the criminal law against the companies employing “children workers” based law Number 23 of 2002 about Protection of child in the Pekanbaru city, And third, attempts what is done in overcoming obstacles to the use of criminal law enforcement “children workers” based law Number 23 of 2002 about Protection of child in the Pekanbaru city. This type of research is classified in legal studies is defined sociological look at the effectiveness of the law in force to see the correlation between law and society, so as to reveal the effectiveness of the enactment of the law in society .From the research and discussion that can disimpilkan First, the implementation of the enforcement of the criminal law agains to companies employing “children workers” was not effectively executed as the number of obstacles in practice is still high so until now the phenomenon of children working always can be found all over. Second, having many barriers, including economic factors that would be a driver of why kids should be working, cultural factors, factors community participation,and lack of coordination and cooperation, government. Third, efforts that can be undertaken by the law enforcement is socialization and coordination of Goverment.Keywords: legal protection, working children